Gemcitabine Plus Anlotinib Is Effective and Safe Compared to Gemcitabine Plus Docetaxel in Advanced Soft Tissue Sarcoma - Liu, Zhiyong; Wang, Xin; Wang, Jiaqiang; Zhang, Peng; Li, Chao; Wang, Bangmin; Liu, Guancong; Yao, Weitao (Frontiers in Oncology, 2022)
Objective: To compare gemcitabine (G) plus docetaxel (D) versus G plus anlotinib (A) for advanced soft tissue sarcoma (STS). Methods: We retrospectively investigated 122 patients with locally advanced or metastatic STS who were treated with either G+D or G+A between July 2016 and October 2021 and compared the efficacy and toxicity of G+D and G+A. The primary endpoints were median progression-free survival (PFS) and the proportion of patients with grade≥3 adverse events. We also analyzed differences in the clinical efficacy of G+D and G+A in leiomyosarcoma, and the differences in the clinical efficacy of G+D and G+A as first-line therapy. Results: Overall, 122 patients were included (81 patients receiving G+D, 41 receiving G+A) with a median age of 55 years. The main histological types are leiomyosarcoma, undifferentiated pleomorphic sarcoma and liposarcoma. After a median follow-up of 25 months, PFS did not differ between patients treated with G+D vs G+A (median PFS:5.8 months and 6.8 months, P=0.39), and overall survival (OS) was similar (median OS:14.7 vs 13.3 months, P=0.75) with similar objective response rate (18.5% vs 14.6%, P=0.17). Whereas, the proportion of patients with grade ≥3 adverse events treated with G+D was significantly more than those treated with G+A (68% vs 44%, P＜0.05). Subgroup analysis of leiomyosarcoma patients (47.5% of the patients) and first-line treatment patients (46.7% of the patients) show that PFS was not significantly different between the two groups (LMS: median PFS:6.5months vs 7.5months, P=0.08; First-line treatment: median PFS:6.2months vs 7.1months, P=0.51). Conclusion: Compared with gemcitabine plus docetaxel for advanced soft tissue sarcoma, gemcitabine plus anlotinib achieved a similar response rate on median progression-free and overall survival, but lower toxicity. These results suggest that gemcitabine plus anlotinib may be an effective and safer strategy for advanced soft tissue sarcoma.